Uruguay Round and its follow-up : building a positive agenda for development : report of a workshop... (UN New YorkUS, 1997)
Highlights what is to be learned from existing country-specific studies in terms of methodology, findings and policy implications; elements of an appropriate policy-oriented framework for country-specific analyses of the effects of the Uruguay Round Agreements and their follow-up on developing countries; and issues to be considered in setting a positive trade agenda for developing countries in future multilateral negotiations.
DC